Integrated approach for smart city index development from concept to indicator weighting - Zialong, Zou; Yan, Li (2018)
Smart city (SC) initiatives are the new megatrend in urban development. Several concepts and frameworks have been proposed to interpret what constitutes smart cities, but they have not yet reached universal acceptance. This study aims to propose a new conceptual
framework for smart cities with an integrated index for better understanding and practical implementation of SC projects. The conceptual framework is proposed after reviewing SC literature under policy analytical method. Based on the framework, an index consisting of six domains, 18 aspects and 36 supporting indicators is proposed. The analytical hierarchy
process (AHP) was applied for indicators weighting for prioritization or key performance indicator (KPI} selections. This study would contribute to more insights in understanding smart cites and their evaluation for policymakers, academia, urban managers and practitioners.
Keywords: Cities and towns -- Growth; Smart cities; Sustainable urban development; Urban planning; Smart City Index